Impacts of pelagic longline fisheries on sea turtles in the Santos Basin, Brazil - Vanucci, Rodrigo Malta; Goldberg, Daphne Wrobel; Maranho, Andrea; Giffoni, Bruno de Barros; Boaventura, Isabella Cristina da Rocha; Dias, Renata Balsamo; Leonardi, Simone Baratto; Neto, Hugo Gallo; Silva, Berenice Maria Gomes; Rogerio, Daniel Wagner; Domit, Camila; Barreto, Andre Silva; et al. (Frontiers in Amphibian and Reptile Science, 2024)
Strand monitoring is valuable for identifying human-caused threats to sea turtles but has limitations in understanding the full range of impacts. To address this, we conducted a survey examining sea turtle interactions with longline fisheries, specifically focusing on hook types used according to target fish species. This study aimed to determine the prevalence of sea turtles with hooks in these fisheries, as well as investigate seasonal and spatial variations in strandings. From August 2015 to December 2020, 4,631 stranded sea turtles were recorded on 2,013 km of monitored beaches in the South and Southeast coasts of Brazil (Caretta caretta, n=3,678, w/hooks=96; Lepidochelys olivacea, n=753, w/hooks=20, and Dermochelys coriacea n=200, w/hooks= 01). Four types of hooks were identified, with a predominance of "J" hooks typically used in the region to capture dolphinfish, Coryphaena hippurus (72/122 hooks). The most affected developmental stages were large juveniles of C. caretta and L. olivacea. The distribution of hooks differed among the states; "J" hooks for catching C. hippurus used in fisheries on the continental shelf were found mostly in São Paulo state, while "circular hooks" for catching swordfish (Xiphias gladius) and "tuna-hooks" for catching tuna (Thunnus spp.) used in fisheries further from the coast were found in states further south. The abundance of "J" type hooks increased during the spring months, aligning with the C. hippurus fishing season. The "J" hooks were located mainly in the esophagus of the stranded turtles (88/122), suggesting that their size and shape enable ingestion by the turtles. In 43.1% of the cases (50/116), necropsies related the death of turtles to the intestinal lesions caused by hooks, fishing lines and/or cables. Despite the small relative frequency of individuals found with hooks (117/4631), pelagic longline fisheries, especially those targeting C. hippurus, are a serious threat to sea turtle populations and, therefore, require specific monitoring and mitigating measures. Furthermore, the number of affected individuals may be underestimated since stranding does not represent total mortality at sea.